2021
DOI: 10.3389/fcimb.2021.700502
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With Remdesivir and Ivermectin Exerts Highly Synergistic and Potent Antiviral Activity Against Murine Coronavirus Infection

Abstract: The recent COVID-19 pandemic has highlighted the urgency to develop effective antiviral therapies against the disease. Murine hepatitis virus (MHV) is a coronavirus that infects mice and shares some sequence identity to SARS-CoV-2. Both viruses belong to the Betacoronavirus genus, and MHV thus serves as a useful and safe surrogate model for SARS-CoV-2 infections. Clinical trials have indicated that remdesivir is a potentially promising antiviral drug against COVID-19. Using an in vitro model of MHV infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Furthermore, the combination of remdesivir with doxycycline reduces virus levels. The authors suggested further studies based on their findings to explore the mechanisms of action of combination therapy, in vivo experiments, and clinical trials in the treatment of SARS-CoV-2 infection [ 70 ]. Baricitinib, in combination with remdesivir, has been reported to be superior to the monotherapeutic use of remdesivir to reduce recovery times and accelerate clinical-status improvement for COVID-19 patients [ 71 ], particularly among those receiving high-flow oxygen or noninvasive ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the combination of remdesivir with doxycycline reduces virus levels. The authors suggested further studies based on their findings to explore the mechanisms of action of combination therapy, in vivo experiments, and clinical trials in the treatment of SARS-CoV-2 infection [ 70 ]. Baricitinib, in combination with remdesivir, has been reported to be superior to the monotherapeutic use of remdesivir to reduce recovery times and accelerate clinical-status improvement for COVID-19 patients [ 71 ], particularly among those receiving high-flow oxygen or noninvasive ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…An individual evaluation of the pure standards of these sterols did not show any antiviral activity, suggesting that the HA inhibitory activity resulted from a synergistic effect among these compounds. The identification of molecules of plant origin and, in particular, the synergistic effect of these molecules should be investigated deeply, as the greater efficiency of combinations of molecules with antiviral effects has been previously reported [ 31 , 32 ]. The most important plant sterols (commonly known as phytosterols) are stigmasterol, campesterol and β-sitosterol [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that a drug combination strategy would help improve antiviral activity. Additionally, the combination of Remdesivir and Ivermectin showed synergism 49,50 . As both Remdesivir and Favipiravir target viral RdRp, their interaction with Ivermectin may represent a similar synergistic mechanism.…”
Section: Favipiravir-chloroquine Combinationmentioning
confidence: 96%